An Exploratory Study as to the Effect of a Leisure Education Program on a Geriatric Day Hospital Patient Population. Issue 2 (2nd April 2016) - Ritcey, Andrew; Singleton, Jerome; Webber, Kristine; King, Andrea; Cook, Jacqueline; Hopper, Tristan
Abstract : This research explored the effectiveness of a leisure education program on participants' overall leisure functioning. The study took place within a Geriatric Day Hospital (GDH) where the goals are to treat and ameliorate patients' symptoms and conditions, while also ensuring promotion of a healthy lifestyle. At the time of the study there were no recreation therapy services provided to the GDH patients. The literature reviewed suggested that a formalized service including leisure education to address leisure awareness, social interaction skills, leisure resources, leisure activity skills, and recreation participation may have significant impact on GDH patients' physical, psychological, and social health. The study design therefore focused on participants' motivation and competence to engage in leisure activities and their personal leisure satisfaction. No significant differences were found between the experimental and control group related to leisure satisfaction and leisure motivation. However, interesting trends were identified in the Leisure Competence Measure. The research also identified useful thematic information collected by the research assistant and interventionist.